PCSK9 targets important for lipid metabolism - Schulz, Rainer (Clin Res Cardiol Suppl, 2017)
Ischemic heart disease is the main cause of death worldwide and it is accelerated by increased low-density lipoprotein (LDL) cholesterol (LDL-C) and/or lipoprotein (a) (Lp(a)) concentrations. Proprotein convertase subtilisin/kexin type 9 (PCSK9) alters both LDL-C and in part Lp(a) concentrations through its ability to induce degradation of the LDL receptor (LDLR). PCSK9, however, has additional targets which are potentially involved in lipid metabolism regulation such as the very low density lipoprotein receptor (VLDL), CD36 (cluster of differentiation 36) and the epithelial cholesterol transporter (NPC1L1) and it affects expression of apolipoprotein B48. The PCSK9 activity is tightly regulated at several levels by factors influencing its transcription, secretion, or by extracellular inactivation and clearance. Many comorbidities (kidney insufficiency, hypothyreoidism, hyperinsulinemia, inflammation) modify PCSK9 expression and release. Two humanized antibodies directed against extracellular PCSK9 received approval by the European and US authorities and additional PCSK9 directed therapeutics (such as silencing RNA) are already in clinical trials. Their results demonstrate a significant reduction in both LDL-C and Lp(a) concentrations – independent of the concomitant medication – and one of them reduced plaque size in high risk cardiovascular patients; results of two ongoing large clinical endpoints studies are awaited. In this review, we summarize and discuss the recent biological data on PCSK9, the regulation of PCSK9, and finally briefly summarize the data of recent clinical studies in the context of lipid metabolism.